Role of native point defects and Ga diffusion on electrical properties of degenerate Ga‐doped ZnO. Issue 10 (27th August 2013) - Doutt, Daniel R.; Balaz, S.; Isabella, L.; Look, D. C.; Leedy, K. D.; Brillson, L. J.
<x xml:space="preserve">Abstract</x> We used a complement of depth‐resolved cathodoluminescence spectroscopy (DRCLS), X‐ray photoemission spectroscopy (XPS), and Hall‐effect measurements to demonstrate the interplay of Zn vacancy‐related (VZn‐R) defects with dopants in degenerately Ga‐doped ZnO grown by pulsed laser deposition. DRCLS VZn‐R/conduction band emission ratios relate to acceptor/donor concentrations, increasing rapidly for growth temperatures >400 °C, evidently because Ga atoms are inhibited from incorporating efficiently on available VZn sites. Elemental XPS depth profiles reveal a temperature‐dependent Ga interface segregation due to Ga bulk diffusion during growth. DRCLS Fermi level thresholds provide a useful indicator of carrier density, revealing depth variations in carrier density that anticorrelate with VZn‐R densities on a nm scale, confirming the acceptor nature of VZn‐R defects.